Three‐Dimensional, Time‐Resolved Profiling of Ferroelectric Domain Wall Dynamics by Spectral‐Domain Optical Coherence Tomography. Issue 8 (10th July 2017) - Haußmann, Alexander; Kirsten, Lars; Schmidt, Sebastian; Cimalla, Peter; Wehmeier, Lukas; Koch, Edmund; Eng, Lukas M.
Abstract : Optical coherence tomography, known for its superb imaging qualities in biomedicine, can also be applied for the precise three‐dimensional mapping and temporal tracking of ferroelectric domain walls. This opens up new possibilities for the comprehensive geometrical characterization of such walls, which is a prerequisite for the thorough investigation of electrical domain wall conductivity in ferroelectrics. Abstract : We apply here spectral‐domain optical coherence tomography (SD‐OCT) for the precise detection and temporal tracking of ferroelectric domain walls (DWs) in magnesium‐doped periodically poled lithium niobate (Mg:PPLN). We reproducibly map static DWs at an axial (depth) resolution down to ∼ 0.6 μm, being located up to 0.5 mm well inside the single crystalline Mg:PPLN sample. We show that a full 3‐dimensional (3D) reconstruction of the DW geometry is possible from the collected data, when applying a special algorithm that accounts for the nonlinear optical dispersion of the material. Our OCT investigation provides valuable reference information on the DWs' polarization charge distribution, which is known to be the key to the electrical conductivity of ferroelectric DWs in such systems. Hence, we carefully analyze the SD‐OCT signal dependence both when varying the direction of incident polarization, and when applying electrical fields along the polar axis. Surprisingly, the large backreflection intensities recorded under extraordinary polarization are not affected by any electrical field, at least for field strengths below the switching threshold, while no significant signals above noise floor are detected under ordinary polarization. Finally, we employed the high‐speed SD‐OCT setup for the real‐time DW tracking upon ferroelectric domain switching under high external fields.